(untitled) (Groundings Undergraduate, 2024)
Denver, Colorado is one of the most rapidly gentrifying cities in the United States. Case studies of gentrifying cities, including Chicago and Los Angeles demonstrate a relationship between urban restructuring and the emergence of youth gangs. However, this phenomenon is under-investigated in Denver. Drawing on an integrative literature review, this paper engages in a critical discussion of the relationship between processes of spatial transformation and youth gang activity in Denver. The contestation of urban space is identified as a central contributor to rising rates of gang criminality in the city’s gentrifying areas. These findings highlight the significance of community activism in popular resistance to gentrification and the protection of residents’ rights to the city.